Opposing Energy Transitions: Modeling the Contested Nature of Energy Transitions in the Electricity Sector. Issue 3 (27th May 2020) - Stefes, Christoph H.
Abstract: Energy transitions are fiercely contested. The incumbents of the fossil‐ and nuclear‐based energy systems have much to lose from a transition to a sustainable and decentralized energy system. They therefore employ their material and political resources to reverse, halt, or slow down this transition. They also attempt to stop and reverse the decentralization of energy production. This article provides a framework that can be used to analyze the contestation that surrounds energy transitions. The analytical framework breaks apart the macro paths of energy transitions, and differentiates between three meso‐paths (political, economic‐technological, and legitimation), emphasizes the feedback processes between these paths, and acknowledges the crucial role that actors play in engendering these feedback processes. It uses Germany as a case study to illustrate the analytical model. It also provides hypotheses that will be tested in the subsequent contributions to this special issue. Abstract : 能源转型方面的争论十分强烈。基于化石和核能的能源系统的在位者会在向可持续和去中心化能源系统转型的过程中损失惨重。因此他们使用各自的物质资源和政治资源来逆转、停止或减缓该转型过程。他们还试图阻止和逆转能源生产的去中心化。本文提供一项能用于分析围绕能源转型争论的框架。该分析框架将能源转型宏观路径分解，区分三条中观路径（政治、经济‐技术、合法化），强调这三条路径之间的反馈过程，承认各行动者在形成这些反馈过程中发挥的关键作用。本文将德国作为案例研究，阐述了该分析框架。本文还就今后有关该特殊议题的研究提出了应被检验的假设。 Abstract : Las transiciones de energía son ferozmente disputadas. Los titulares de los sistemas de energía basados en combustibles fósiles y nucleares tienen mucho que perder de una transición a un sistema energético sostenible y descentralizado. Por lo tanto, emplean sus recursos materiales y políticos para revertir, detener o ralentizar esta transición. También intentan detener y revertir la descentralización de la producción de energía. Este artículo proporciona un marco que puede usarse para analizar la contestación que rodea las transiciones de energía. El marco analítico rompe los macro caminos de las transiciones de energía, y diferencia entre tres caminos meso (político, económico‐tecnológico y de legitimación), enfatiza los procesos de retroalimentación entre estos caminos y reconoce el papel crucial que juegan los actores para generar estos comentarios. procesos. Utiliza Alemania como un caso de estudio para ilustrar el modelo analítico. También proporciona hipótesis que se probarán en las contribuciones posteriores a este número especial.